THE EDUCATIONAL VALUES OF WORSHIP OF PRAYER - Aimi - (Politeknik Negeri Sriwijaya, 2017)
Islamic Education Study Program. Currently, some Muslims have less realizing the true meaning of education from worship of prayer in congregation. The person who has understood the meaning of education in worship in congregation, his mind, attitude and his way of thinking must be in accordance with the guidance of al-Qur'ân and Hadith. Thus, how important is the significance and meaning of prayer for a servant to Allah swt. Praying is said to be something of the greatest , since prayer involves three human components at once; first, body movements; second, oral speech; and thirdly, the inner adoration, which are all directed to Him. The order to perform the prayer was revealed when the Prophet Muhammad saw did Isra' Mi'raj. Prayer is the most important mean to complain about all of human problems to Allah swt. Praying in congregation indirectly trains us to be discipline, holy, patient and to strengthen the sense of brotherhood among Muslims. Patience and prayer are the wisest and most effective way for a Muslim to deal with the problems and trials that override him so that his anxiety will not become prolonged.